JAVANESE LANGUAGE DEVELOPMENT THROUGH CAMPURSARI: FERGUSON’S LANGUAGE PLANNING PERSPECTIVE - Endang Sri Maruti (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study attempted to describe the forms of Javanese language development through campursari songs based on Ferguson’s language planning theory. This study used a descriptive qualitative design where the data were collected with the documentation method, that was to collect words, phrases, clauses, and sentences from campursari song lyrics containing elements of development. Data analysis was performed using sharing method with substitution techniques. The results of the analysis showed that the Javanese language development was divided into two forms. The first form was graphization through the establishment of pronunciation and spelling by intensifying Latin words to write either vocal or consonant Javanese words in texts. The second form was modernization through lexicon extension where the Javanese language underwent a shift in the use of old terms and language extensification that was marked by the emergence of novel words or terms. The Javanese language development forms were affected by some factors, including the development of the Javanese society social life as well as the Indonesian language intervention and integration. This has become part of shared agreement to maintain the Javanese language existence both in the present and for the future.